Learn Solve By Substitution Y X2 3x 7 3x Y 2

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Solve by Substitution y=x^{2}+3x-7, 3x-y=-2

**Solution:**

Given are the linear equations in two variables.

y = x^{2}+ 3x - 7 ----> (1)

3x - y = -2 ----> (2)

Let us use substitution method to solve these equations.

3x - y = 7- x²

⇒ -2 = 7- x²

⇒ -2 - 7 = -x²

⇒ -9 = -x²

x= ±3

Put x= ±3 in (1), we get

3x - y= -2 ⇒ 3( ±3) -y = -2

⇒ ±9 -y =-2

⇒ ±9+2 = y

y= 11, -7

## Solve by Substitution y=x^{2}+3x-7, 3x-y=-2

**Summary: **

Solving by Substitution y=x^{2}+3x-7, 3x-y=-2 we get x= ±3 and y= 11, -7.

Math worksheets and

visual curriculum

visual curriculum